Proton conductivity studies in metal-organic frameworks - Pili, Simona (2015)
This Thesis describes the synthesis and characterisation of novel metal-organic frameworks designed for proton conductivity applications. A new system for impedance measurements was constructed and tested, and the proton conductivity of a variety of MOFs was studied. Additionally, the effect of ligands with phosphonate functional groups, the strategic choice of metal ions and the use of proton carrier guests loaded in the pores of MOFs to obtain conducting materials was investigated. Chapter 1 introduces the current challenges in energy sustainability and endorses fuel cells as an alternative energy source. A careful description of the proton exchange membrane (PEM), key component of fuel cells, with emphasis on the materials currently used in industry is discussed. The need to overcome the limitations of PEMs under the working conditions and understanding the molecular mechanism of proton conduction is crucial for the design of new materials with improved proton conductivity properties. Recently, metal-organic frameworks (MOFs) have been pointed as alternative candidates for proton conduction application. Their crystalline nature combined with the possibility to design their structures by choosing opportune functional groups and proton-carrier guests make them promising candidates as proton conducting materials. Chapter 2 presents a brief introduction of Electrochemical Impedance Spectroscopy (EIS), the main technique used to evaluate the proton conductivity of the MOFs in Chapters 3, 4 and 5. An overview of the physical basis of EIS and the data analysis strategies are discussed. In the second part of Chapter 2 the newly designed experimental set up employed to measure the proton conductivity of MOFs is described with emphasis on the design of the conductivity cell, control of temperature and relative humidity, and sample preparation. The calibration of the experimental set up was performed using imidazole, a readily available linker with known conductivity. In Chapter 3 the synthesis and structural characterisation of two new isostructural phosphonate-based MOFs,[Ni3(H3L1)2(H2O)10.5(DMF)3]and[Co3(H3L1)2(H2O)10.4(DMF)3](H6L1= benzene-1,3,5-p-phenylphosphonic acid), denoted as NOTT-500(Ni) and NOTT-500(Co), are described. X-ray structural analysis revealed that these materials have acidic phosphonate groups (P-OH) and water molecules coordinated to the metal ions (M-OH2) organised in an efficient proton-hopping pathway. TGA, VT-PXRD and solid-state UV-visible analyses showed a reversible structural phase transition associated with a marked change in colour upon dehydration-hydration of NOTT-500(Ni, Co). Proton conductivity measurements were performed exhibiting values of 1.11(03) x 10-4 S cm-1 and 4.42(06) x 10-5 S cm-1 forNOTT-500(Ni) and NOTT-500(Co) respectively, at 99 % RH and 25 o C. The activation energy of the proton transfer process for NOTT-500(Ni) was determined over the temperature range of 18-31 o C at 99 % RH, giving a value of 0.46 eV which indicates the proton conduction occurs through the combination of the Grotthuss and Vehicle mechanisms. Quasi-elastic neutron scattering (QENS) experiments on NOTT-500(Ni) under anhydrous conditions (0 % RH) suggested that the proton transfer in the hopping pathway (regulated by the Grotthuss mechanism) is well described by a “Spherical free diffusion” model, with an activation energy of 0.076 eV. Chapter 4 introduces two novel approaches to enhance the proton conductivity of a new family of lanthanide MOFs, [M (HL2)] (H4L2= biphenyl-4,4'-diphosphonic acid ; M = La, Ce, Nd, Sm, Gd, Ho). The first method aims to increase the concentration of protons in a fixed volume of MOF by using the shorter version of the organic ligand, benzene-1,4-diphosphonic acid, H4L3, with subsequent improvement of the proton conductivity properties in [M(HL3)] (M = La, Ce, Nd, Sm, Gd, Ho). The second method to achieve better proton conductivity was carried out by substituting 3+ metal ions, Ln (III), with a 2+ metal, Ba (II), leading to the synthesis of an isostructural complex [Ba(H2L2)] with increased number of protons in comparison with [M(HL2)]. The proton conductivities of [M (HL3)] (10-4 S cm-1) and [Ba (H2L2)] (10-5 S cm-1) exhibited a significant increase when compared with [M (HL2)] (10-6 S cm-1) at 25 o C and 99 % RH. Extensive impedance studies at different temperatures and relative humidities were performed together with full characterisation of all the materials presented in this Chapter. Chapter 5 describes a preliminary study of two new complexes synthesised through postsynthetic modification of the well-known MOF, NOTT-300(Al). The addition of imidazole (a proton carrier) into the 1D channels was performed using two different approaches; the vapour diffusion (d) and solvation methods(s). Impedance studies of the post-synthetically modified complexes, Im@NOTT-300(Al)-(d) and Im@NOTT-300(Al)-(s), both with formula {Al2(OH)2(C16O8H6)(Al2O3)(CH4O)2(C3N2H4)0.61}∞, were investigated. The experimental results showed that at 20 o C and 99 % RH the proton conductivity of Im@NOTT-300(Al)-(d) (2.39(11) x 10-5 S cm-1) and Im@NOTT-300(Al)-(s)(1.37(13) x 10-5S cm-1) is two orders of magnitude higher compared with NOTT-300(Al) (1.08(10) x 10-7 S cm-1). These preliminary studies suggested the postsynthetic modification of porous MOFs with proton-carrier guest molecules is a promising direction for further research in this area. In Chapter 6 is summarised the work presented in this thesis.